2015
DOI: 10.1167/iovs-14-16184
|View full text |Cite
|
Sign up to set email alerts
|

Slit2 Promotes Angiogenic Activity Via the Robo1-VEGFR2-ERK1/2 Pathway in Both In Vivo and In Vitro Studies

Abstract: Slit2 overexpression promoted angiogenic effects in both a laser-induced CNV mouse model and HUVECs and promoted the biological activity of endothelial cells. Slit2 may promote angiogenesis by upregulating Robo1 and activating the VEGFR2-ERK1/2 pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 33 publications
1
33
1
Order By: Relevance
“…In fact, when we interfered with Slit2/Robo4 signalling, SSc-MVECs exhibited a significant improvement in their ability to proliferate, migrate and form capillary-like structures in vitro. In endothelial cells, Slit2/Robo4 axis was found to prevent the activation of MAP kinases,16 Arf small GTPases21 or Src family kinase (SFK)18 mediated by proangiogenic factors such as VEGF 45. In this context, we observed that treatment of H-MVECs with Slit2 reduced p-Src to levels comparable with those of basal SSc-MVECs, suggesting that this secreted glycoprotein may suppress angiogenesis through the inhibition of SFK signalling pathways.…”
Section: Discussionmentioning
confidence: 75%
“…In fact, when we interfered with Slit2/Robo4 signalling, SSc-MVECs exhibited a significant improvement in their ability to proliferate, migrate and form capillary-like structures in vitro. In endothelial cells, Slit2/Robo4 axis was found to prevent the activation of MAP kinases,16 Arf small GTPases21 or Src family kinase (SFK)18 mediated by proangiogenic factors such as VEGF 45. In this context, we observed that treatment of H-MVECs with Slit2 reduced p-Src to levels comparable with those of basal SSc-MVECs, suggesting that this secreted glycoprotein may suppress angiogenesis through the inhibition of SFK signalling pathways.…”
Section: Discussionmentioning
confidence: 75%
“…The SLIT2/ROBO pathway has been associated with retinal neovascularization, proliferative diabetic retinopathy, and RPE cells, 31,32 as well as adipose-secreted SLIT2-C fragments that regulate thermogenesis and metabolic function of brown and beige fat. 24 The secreted SLIT2 and SLIT2-N fragments promoted retinal neovascularization in the developing retina and abnormal pathologies in diabetic retinopathy.…”
Section: Discussionmentioning
confidence: 99%
“…First, we focused on ROBO4 and did not address the role of Slit2–ROBO1 signalling, which has been shown to be pro-angiogenic [45]. Second, the in vivo overexpression approach is not specific for endothelial cells.…”
Section: Discussionmentioning
confidence: 99%